Metal interactions between the polychaete Branchipolynoe seepensis and the mussel Bathymodiolus azoricus from Mid-Atlantic-Ridge hydrothermal vent fields - Bebianno, Maria João (2020)
The vent blood-red commensal polynoid polychaete Branchipolynoe seepensis is commonly found in the pallial cavity of the vent mussel Bathymodiolus azoricus, the dominant bivalve species along the Mid-Atlantic-Ridge (MAR) and is known to be kleptoparasitic. Mussels were collected from three hydrothermal vent fields in the MAR: Menez Gwen (850 m depth, MG2, MG3 and MG4), Lucky Strike (1700 m depth, Montségur-MS and Eiffel Tower-ET) and Rainbow (2300 m depth). Polychaetes were absent in all Menez Gwen vent mussels, while the highest percentage was detected in mussels from Lucky Strike, where more than 70% of the mussels had at least one polychaete in their mantle cavity, followed by Rainbow with 33% of mussels with polychaetes. Total metal concentrations (Ag, Cd, Co, Cu, Fe, Mn, Ni and Zn) were determined in polychaetes whole body and in the mussel tissues (gills, digestive gland and mantle). To understand the possible metal interactions between symbiont and host, the activity of antioxidant defence (catalase (CAT), metallothioneins (MTs)), biotransformation enzymes (glutathione-s-transferases (GST)) activities and lipid peroxidation (LPO) were determined in polychaete whole soft tissues and in mussel tissues (gills, digestive gland and mantle). Metal concentrations in polychaetes and mussels tissues indicated that the accumulation patterns were species specific and also influenced by, and possibly dependent upon, the inter- and intra-variation of vent physico-chemistry between hydrothermal fields. Despite not detecting any strong correlations between metal and enzymes activities in polychaetes and mussels, when in presence of polychaetes, mussels presented less metal concentrations in the gills and digestive gland and lower activity of enzymatic biomarkers. This leads to infer that the polychaete plays a role on the detoxification process, and the interaction between the polychaete mussel association is probably an adaptation to metals concentrations at the vent sites.